2005
DOI: 10.1063/1.1999851
|View full text |Cite
|
Sign up to set email alerts
|

Debris mitigation in a laser-produced tin plume using a magnetic field

Abstract: Debris mitigation in a laser-produced tin plume is one of the most important issues for its use as an extreme ultraviolet source in next generation lithography. We investigated the use of a magnetic field for controlling the kinetic energies of various species in a laser-produced tin plasma. 1.06 m, 8-ns pulses from a Nd:yttrium aluminum garnet laser were used to create the tin plasma in vacuum that expanded across a transverse magnetic field. Time-of-flight optical emission spectroscopy was used to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 16 publications
(17 reference statements)
1
27
0
Order By: Relevance
“…The debris includes fast ions and neutrals, clusters, and out of band emission and, hence, controlling the expanding plume species is indeed a greatest challenge for future LPP EUV light source. We employed various methods for controlling and/or mitigating energetic ions including; low-density targets, 4,17 ambient gas, 16 magnetic field, 18 pre-pulse 2 and synergetic effects ͑combina-tion of two methods͒. 16 We recently reported that the spot size has negligible effect on the conversion efficiency ͑CE͒ of in-band radiation ͑13.5 nm with 2% bandwidth͒.…”
Section: Introductionmentioning
confidence: 99%
“…The debris includes fast ions and neutrals, clusters, and out of band emission and, hence, controlling the expanding plume species is indeed a greatest challenge for future LPP EUV light source. We employed various methods for controlling and/or mitigating energetic ions including; low-density targets, 4,17 ambient gas, 16 magnetic field, 18 pre-pulse 2 and synergetic effects ͑combina-tion of two methods͒. 16 We recently reported that the spot size has negligible effect on the conversion efficiency ͑CE͒ of in-band radiation ͑13.5 nm with 2% bandwidth͒.…”
Section: Introductionmentioning
confidence: 99%
“…In an EUVL tool, the collector mirror is expected to be placed ϳ15-20 cm from the plasma source. For industrializing EUVL, a lifetime of more than 10 9 shots is needed for the collector mirror. So controlling the debris from laser plasma is the most important task for creating a clean photon source for EUVL.…”
Section: Introductionmentioning
confidence: 99%
“…The normalized radial wave functions derived from the use of the invariant operator are represented as Equation (27) with Equations (22) and (28). An interesting mathematical feature in this case is that the quantum solutions are expressed in terms of the complex classical solutions of Equation (9).…”
Section: Resultsmentioning
confidence: 99%
“…We can see that angular momentum of the particle is conserved in variable magnetic fields as well as in the static limit [7]. Several interesting phenomena that take place by the presence of magnetic field in an ionized plasma include plume confinement, particle acceleration and deceleration, dissipation of kinetic energy into thermal energy, Debris mitigation, and instability of plasma [8][9][10].…”
Section: Hamiltonian Dynamicsmentioning
confidence: 98%